Profil Penguasaan Keterampilan Proses Sains Mahasiswa Program Pendidikan Guru Sekolah Dasar Universitas Terbuka - Afif Kurniawan; Fadloli Fadloli (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Individuals benefit from science process skills while trying to solve problems through research. To solve these problems individuals must acquire sufficient science process skills. Teachers must be able to understand these skills so that students can obtain the required proficiency. This study aims to determine the science process skills of undergraduate students S1 study Primary School Teacher Education Open University as well as an elementary school teacher in terms of gender and years of service. This quantitative study was conducted with the survey. The study sample consisted of 120 students of S1 study Primary School Teacher Education Open University as well as an elementary school teacher. Researchers obtain study data based on the results of tests of Science Process Skills (SPS). The test consists of 17 questions SPS understanding of the concept of SPS and 25 about the use of SPS. The results of the study revealed that the students SPS Primary School Teacher Education Open University as well as elementary school teachers are not sufficient. It also indicates that the student scores Science process skills Elementary School Teacher Education Program Open University as well as elementary school teachers did not differ significantly by gender and  differed significantly by year of service. This study suggests doing a tutorial model development to develop science process skills of undergraduate students S1 study Primary School Teacher Education Open University as well as an elementary school teacher until the desired level.Keywords:       science process skills, elementary school teacher, gender, year of service